The Prohibition of Asking Positions in Hadith: Perspectives from Banjarmasin City Ulema - Muhammad Torieq Abdillah; Hayatun Na'imah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This research was conducted in the city of Banjarmasin against the backdrop of political turmoil during the 2020 Pilkada for Mayor and Deputy Mayor of Banjarmasin. The Pilkada results were disputed and reported to the South Kalimantan Bawaslu and the Constitutional Court. Moreover, there are numerous hadiths that address the prohibition of seeking positions of power. If interpreted literally, these hadiths clearly prohibit such actions, making it essential to seek the opinions of scholars, including those from Banjarmasin City. This empirical juridical research, employing a legal sociology approach, involved eight Banjarmasin city scholars as subjects and focused on the hadith concerning the prohibition of seeking positions as the object. The study was conducted through observation, interviews, and documentation, followed by data collection and descriptive analysis. The results indicate that the majority of Banjarmasin City scholars interpret the hadith on the prohibition of seeking positions both textually and contextually. These scholars adhere to the interpretations (syarah) of previous scholars. Furthermore, the majority believe that running for leadership in a democratic system and asking for office can be either the same or different, depending on the specific conditions. Some scholars see similarities between the two, while others do not.